A rare case of giant endometrioma-with ultrasound features mimicking malignancy - Bhatia, Ruby; Shah, Pooja; Goel, Rishu; Tewari, Vidushi; Malik, Sanjum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian endometriomas are common in women of reproductive age but rarely exceed 6 cm in diameter. Ovarian endometrioma exceeding 10 cm in dimension are referred as giant endometrioma. They are rare and pose a major diagnostic dilemma to the clinicians. We present a rare case of ovarian endometrioma of 18.7 cm in largest diameter, with internal septations, with a solid component, with low grade neovascularization on ultrasonography having RMI I score of 294 suggesting risk of malignancy, and IOTA simple rules suggesting the mass as inconclusive in nature, and the diagnosis of a benign mass was made on frozen section and confirmed as endometrioma on postoperative histopathologic examination. The challenges in making diagnosis of a huge ovarian endometrioma are highlighted and various literature on giant ovarian endometrioma are reviewed.